Survival and autoimmune risks post-thymectomy - Tsirkin, Irina; Khateb, Mohamed; Aran, Dvir; Kaz, Amit; Shelly, Shahar (Frontiers in Immunology, 2025)
Background and objectivesRecent studies have raised concerns about thymectomy's deleterious effects. However, this conclusion was not exclusive to patients with myasthenia gravis (MG). The objective of this study was to test this hypothesis in thymectomy patients, regardless of their MG status.MethodsWe conducted a retrospective case-control study to analyze clinical and radiological data from 1 January 2010 to 30 November 2023. Patients were divided into four groups: MG with (MG-Thy) or without thymectomy (MG-NO-Thy); thoracoscopic surgery without thymectomy (Surgery-NO-Thy) and Non-MG with thymectomy (Non-MG-Thy).ResultsWe identified a total of 456 patients (n=41, MG-Thy; n= 278, MG-NO-Thy; n=65, Non-MG-Thy; and n=72, Surgery-NO-Thy). The median ages were as follows: MG-Thy, 45.6 years (range: 22-79); MG-NO-Thy, 65 years (13-93); Non-MG-Thy, 59.8 (19-85) years; and Surgery-NO-Thy, 59.8 years (range: 19-85) (p<0.001). The median follow-up times were 5.5 years in MG-Tym, 3 in MG-NO-Thy, 3.9 in Non-MG-Thy, and 4.7 years in Surgery-NO-Thy. A thymic mass was detected with chest computed tomography (CT) in 56% (23/41) of the MG-Thy cohort and in all the Non-MG-Thy cohort. Thymic pathology in the MG-Thy group showed normal/fat atrophic thymus in 31.7% (13/41), hyperplasia in 26.8% (11/41), thymic cyst in 2.4% (1/41), and malignant in 39% (16/41). Thymic pathology in the non-MG group showed hyperplasia, fat, or normal thymus in 16.9% (11/65); thymic cyst in 18.5% (12/65); malignant thymoma in 60% (39/65); and others in 4.6% (3/65). The death rate was the lowest in the MG-Thy group, compared to the non-MG groups and the MG-No-Thy group. Specifically, death occurred in zero cases in the MG-Thy group, while it occurred in 13.8% (9/65) of the thymectomized non-MG group and in 35.6% (99/278) of the MG-without thymectomy group. Excluding late-onset MG patients (LOMG), the death incidence was 14.4% (15/104). The prevalence of autoimmune diseases before thymectomy was 14.6% (6/41) in the MG-Thy group versus 12.3% (8/65) in the Non-MG-Thy group, with three new cases post thymectomy in non-MG group. Post thymectomy cancer incidence was zero in the MG-Thy group, versus 16.2% (45/278) in the MG-NO-Thy group.ConclusionThe benefits of thymectomy outweigh potential risks for patients with MG or patients with thymic malignancies. Incidental thymectomy should be avoided. This call for reevaluation of thymectomy especially for non-neoplastic causes.